IMPLEMENTASI PROSEDUR PENYELESAIAN SENGKETA PADA PEMILIHAN UMUM - Rendi Adi Pratama, Nugroho; Santosa (MAJAPAHIT POLICY, 2023)
Every election law enforcement is handled by state institutions depending on the type of violation committed. Bawaslu is wrongan institution that obtains attribution of authority to enforce election laws related to election process disputes. On implementationIn its authority, Bawaslu is considered to often take actions that go beyond what should be done. And this research usesQualitative research methods have the meaning of being a scientific way to obtain valid data, and with the aim of finding,developed, or proven, a certain knowledge or object so that it can be used or understood to solve, and anticipateproblems in a particular field or object. With Bawaslu's review as a very important role in overseeing electionsgeneral in accordance with what is mandated in the Law on Election Management, which states that the supervisory function ofgeneral elections which are described or explained in the duties, authority, obligations of election supervisors, and resolution of problems or disputescontained in it which includes general elections.